(untitled) (TAMADDUN NURI JURNALI, 2025)
This article is devoted to the analysis of the oriental criteria of our values in the works of Uzbek intellectual philosophers. The article analyzes how the moral teachings of "Avesta", the concepts of social justice, goodness and the fight against evil are reflected in the works of Uzbek intellectuals. Also, the impact of these values on the development of national consciousness and society is considered.